Christen in Ägypten - Behlmer, Heike; Tamcke, Martin, 1955- (Göttinger Orientforschungen. Ägypten, 2015)
Christians in Egypt originates from a series of lectures at the University of Göttingen on the history and present of the Christian communities in the Middle East. The series of lectures, which is going into its third year, is a joint event of the Chair for Ecumenical Theology and Oriental Church and Mission History and the Seminar for Egyptology and Coptic Studies and is dedicated to the entire spectrum and the two-thousand-year history of Christianity in the Near and Middle East - a religious diversity that today faces an uncertain future. The first of the series of lectures in the 2013 summer semester covered the history of Egyptian Christians from the first centuries after Christ to the "Arab Spring". , but also other Christian denominations on Egyptian soil.The eleven articles in Christians in Egypt highlight ancient monasticism and the church politics of Patriarch Athanasius in the 4th century as well as the Protestant mission in Egypt in the 20th century and the contested issue of church building in a Muslim majority society.